Producción y caracterización de los influencers sénior españoles en instagram - Dr. Francisco Marcos MARTÍN MARTÍN,Dra. Lucía BALLESTEROS AGUAYO,Dra. Encarnación PEDRERO GARCÍA,Dra. Rocío CRUZ DÍAZ (Fonseca, Journal of Communication, 2023)
The purpose of our research is to determine the presence of Spanish senior instagrammers, as well as to analyse the areas in which they exert influence. To achieve this objective, we used an exploratory qualitative methodology through content analysis to study the characteristics of the production of the 12 profiles of senior influencers with more than 100,000 followers